POLITENESS IN USING SIMALUNGUNESE PERSONAL SUBJECT PRONOUNS - Evi Irawanti Saragih; Sri Minda Murni; Sumarsih Sumarsih (State University of Medan, 2019)
This study aimed to reveal and explain politeness in using simalungunese personal subject pronouns by trying to find out the type mostly used, the way and the reason of people in Galang City using it. This study was qualitatively conducted that taken 35 people of Galang City as respondent/participant. The data was collected by using questionnaire paper. The findings of this study showed that Simalungunese Personal Subject Pronouns people in Galang City mostly used were First Personal Subject Pronouns Ahu/au with 130 times chosen (46%), Second Personal Subject Pronouns Ham/Handian/Nassiam with 159 times chosen (57%), Third Personal Subject Pronouns Ia/Sidea with 128 times chosen (46%). The ways of people in Galang City using Simalungunese Personal Subject determine by gender, Situation, Age, and Familiarity. The reason of people in Galang city using Simalungunese personal subject pronouns were making no distance/gap, adapting the situation, knowing the rule of communication, learning from family. The findings of this study revealed that four parameters of politeness influenced chosen of pronouns, and the use of Simalungunese Personal Subject pronouns itself influenced the level of politeness. Keywords : Politeness , Simalungunese , Personal Pronouns